Education Management the Perspective Quran - Rahmat Rahmat; Faizal Efendi; Odsisa Putera; Yumna Yumna (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
Education management is very essential in educational activities. Scientifically, educational management experts and educational practitioners have written many books related to educational management. However, not much is known about educational management from the perspective of the Quran. In fact, the Quran is a holy book which contains instructions for humans in carrying out life in this world until the afterlife. Based on its function, management is divided into five divisions, namely: planning, organizing, implementing, monitoring and evaluating. Each of these functions becomes a flow in management and is closely related to each other. If one function is weak, it will greatly affect the other functions. For each management function there are several related verses from the Quran. This shows that the Quran also provides hints about these management functions. This research uses a qualitative method with a thematic analysis approach. Furthermore, to strengthen the analysis and discussion the author also refers to books, expert opinions and various findings from previous researchers related to this issue and topic. There are two types of management that researchers describe in the view of the Quran, namely Total Quality Management and Management Based School. Total Quality Management is a theory that emphasizes quality obtained through solid and reliable leadership. Temporary Management Based School emphasized that the management of institutions should be delegated to implementers in the field, namely schools.